Enhanced Resistance to Cucumber mosaic virus in the Arabidopsis thaliana ssi2 Mutant Is Mediated via an SA-Independent Mechanism - Ken-Taro Sekine; Ashis Nandi; Takeaki Ishihara; Shu Hase; Masato Ikegami; Jyoti Shah; Hideki Takahashi (Molecular Plant-Microbe Interactions, 2004)
The Arabidopsis thaliana SSI2 gene encodes a plastid-localized stearoyl-ACP desaturase. The recessive ssi2 mutant allele confers constitutive accumulation of the pathogenesis-related-1 (PR-1) gene transcript and salicylic acid (SA), and enhanced resistance to bacterial and oomycete pathogens. In addition, the ssi2 mutant is a dwarf and spontaneously develops lesions containing dead cells. Here, we show that the ssi2 mutant also confers enhanced resistance to Cucumber mosaic virus (CMV). Compared with the wild-type plant, viral multiplication and systemic spread were diminished in the ssi2 mutant plant. However, unlike the ssi2-conferred resistance to bacterial and oomycete pathogens, the ssi2-conferred enhanced resistance to CMV was retained in the SA-deficient ssi2 nahG plant. In addition, SA application was not effective in limiting CMV multiplication and systemic spread in the CMV-susceptible wild-type plant. The acd1, acd2, and cpr5 mutants which, like the ssi2 mutant, accumulate elevated SA levels, constitutively express the PR-1 gene, spontaneously develop lesions containing dead cells, and are dwarfs, are, however, fully susceptible to CMV. Our results suggest that dwarfing, cell death, and constitutive activation of SA signaling are not important for the ssi2-conferred enhanced resistance to CMV. However, the sfd1 and sfd4 mutations, which affect lipid metabolism, suppress the ssi2-conferred enhanced resistance to CMV, thus implicating a lipid or lipids in the ssi2-conferred resistance to CMV. Interestingly, the ssi2-conferred resistance to CMV was compromised in the ssi2 eds5 plant, suggesting the involvement of an SA-independent, EDS5-dependent mechanism in the ssi2-conferred resistance to CMV.